2014
DOI: 10.1111/cns.12294
|View full text |Cite
|
Sign up to set email alerts
|

(R)‐alpha‐methylhistamine Suppresses Inhibitory Neurotransmission in Hippocampal CA1 Pyramidal Neurons Counteracting Propofol‐Induced Amnesia in Rats

Abstract: Our results suggest that RAMH, by inhibiting presynaptic GABAergic neurotransmission, suppresses inhibitory neurotransmission in hippocampal CA1 pyramidal neurons, which in turn reverses inhibition of CA1 LTP and the spatial memory deficits induced by propofol in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…In the present study, we obtained several sets of data about the role of the key molecular cAMP in the propofol induced LTP inhibition and memory impairment. First, consistent with the results that propofol inhibited cAMP dependent LTP in the hippocampal CA1 region (Nagashima et al, 2005 ; Li et al, 2014 ), propofol inhibited the FSK induced LTP in the hippocampal CA1 region. It further endorsed the assumption that propofol inhibited cAMP signaling induced CA1 LTP.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In the present study, we obtained several sets of data about the role of the key molecular cAMP in the propofol induced LTP inhibition and memory impairment. First, consistent with the results that propofol inhibited cAMP dependent LTP in the hippocampal CA1 region (Nagashima et al, 2005 ; Li et al, 2014 ), propofol inhibited the FSK induced LTP in the hippocampal CA1 region. It further endorsed the assumption that propofol inhibited cAMP signaling induced CA1 LTP.…”
Section: Discussionsupporting
confidence: 87%
“…Long-term potentiation (LTP), which is the long-lasting increase in synaptic strength following trains of stimuli, has been proposed to be as a cellular mechanism of memory formation in the brain (Eichenbaum, 1996 ; Miller and Mayford, 1999 ). Previous researches from ourselves and others found that propofol could inhibit theta burst stimulation induced hippocampal CA1 LTP in both rats and mice (Nagashima et al, 2005 ; Takamatsu et al, 2005 ; Li et al, 2014 ), but had little effect on the CA1 LTP evoked by high frequency stimulations (Li et al, 2014 ). It has been proved that different protocols induced LTP have different underlying molecular mechanisms (Nguyen and Kandel, 1997 ; Staubli et al, 1999 ; Costa and Grybko, 2005 ; Li et al, 2014 ).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…H 3 receptor functional analysis, using an H 3 receptor agonist (R)-α-MeHA, revealed that in fully differentiated 7-day myotubes, H 3 receptor activation decreased Ca 2 þ imaging evoked by electrical stimulation. The lowest (R)-α-MeHA concentration used (1 nM) was below the agonist affinity for H 3 receptor (pK i ¼ 8.4) in the brain (Chen et al, 2003 andLi et al, 2014) and had no effect on the cytoplasmic Ca 2 þ imaging under electrical stimulation in our study. On the other hand, the highest (R)-α-MeHA concentration used (100 μM) was also less active, probably because of combinatorial effects, due to nonspecific activation of other receptors (H 1 receptor or H 2 receptor) on the cell membrane (Chen et al, 2015), which counteracted the response (Leurs et al, 1998), or probably as a self-protective mechanism.…”
Section: Discussionmentioning
confidence: 54%